Another potential source of destructive earthquakes and tsunami offshore of Sumatra - Wiseman, Kelly (2012)
We link geodetic data from the Sumatran GPS Array (SuGAr) and earthquake focal mechanisms to show that a 900-km long backthrust, arising from the Sunda megathrust offshore of Sumatra, has recently become active following the series of great megathrust earthquakes of this past decade. Shallow failure of the Mentawai backthrust explains coseismic displacements during moderate-earthquake clusters in 2005 and 2009. These two clusters represent the first activity on the backthrust in more than 30 years. Existing paleogeodetic evidence of vertical deformation in past centuries is too sparse to characterize earlier major activity, but leaves open the possibility of historic great backthrust earthquakes. Our geodetic evidence for rupture of the Mentawai backthrust during the two recent earthquake clusters suggests that this large fault may well pose an additional seismic and tsunami hazard to the coastal communities of central Sumatra.